Elements of strength of materials - Timoshenko, Stephen (Van Nostrand, 1935)
This book gives a good introduction to solid mechanics. Especially the topics on superposition principles for beam deflection calculations, energy methods & castiglino's theorem are clearly explained. This book is among the few I have read(and solved all the excercises) from cover to cover. I think it should be on the shelf of every engineer.